2023
DOI: 10.3390/ijms24108632
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Cardiomyopathies and Cardiac Defects in Inherited Disorders of Carbohydrate Metabolism: A Systematic Review

Federica Conte,
Juda-El Sam,
Dirk J. Lefeber
et al.

Abstract: Heart failure (HF) is a progressive chronic disease that remains a primary cause of death worldwide, affecting over 64 million patients. HF can be caused by cardiomyopathies and congenital cardiac defects with monogenic etiology. The number of genes and monogenic disorders linked to development of cardiac defects is constantly growing and includes inherited metabolic disorders (IMDs). Several IMDs affecting various metabolic pathways have been reported presenting cardiomyopathies and cardiac defects. Consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 666 publications
(509 reference statements)
0
3
0
Order By: Relevance
“…PIGA participates in phosphatidylinositol production on the endoplasmic reticulum membrane based on N-acetylglucosamine synthesis. Inherited metabolic disorders 37 heavily rely on this reaction. The discovery of UQCRQ suggests that it could serve as a potential biomarker for predicting the response to abatacept/methotrexate in RA patients 38 .…”
Section: Discussionmentioning
confidence: 99%
“…PIGA participates in phosphatidylinositol production on the endoplasmic reticulum membrane based on N-acetylglucosamine synthesis. Inherited metabolic disorders 37 heavily rely on this reaction. The discovery of UQCRQ suggests that it could serve as a potential biomarker for predicting the response to abatacept/methotrexate in RA patients 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Candidate genes overlapping between this study and genes with de novo variants in the Sifrim et al and Homsy et al exome studies. Genes CTBP1[20] and ATP6V1E1[21] were also found to cause CHD but did not overlap with the exome studies.…”
mentioning
confidence: 81%
“…Beta-1,3-glucuronosyltransferase (B3GAT3), the first cloned glycosyltransferase, plays a pivotal role in the biosynthesis of sulfated GAGs, converting core proteins into functional PGs and GAGs. Numerous studies have implicated B3GAT3 as an oncogenic factor in cancer development. For example, increased expression of CS biosynthetic enzymes, including B3GAT3, has been noted in colon and rectal adenocarcinomas . In addition, Zhao et al identified B3GAT3 as an independent risk factor for HCC by analyzing nine genes linked to amino acid metabolism .…”
Section: Introductionmentioning
confidence: 99%